Pengaruh Kepribadian, Kontrol Diri, Kesepian, dan Jenis Kelamin Terhadap Penggunaan Internet Kompulsif Pada Remaja - Ulfah, Dara Mutia; Nisa, Yunita Faela (‎‎‎TAZKIYA: Journal of Psychology, 2015)
Compulsive internet use on teenagers is a challenging topic in research these days. Howpsychology explains this behavior becomes really important to study on and to controlcompulsive internet use on teenagers. Objective of this study is to determine significance ofpersonality effect (extraversion, agreeableness, neuroticism), self-control, loneliness, and genderon compulsive internet use on teenagers. Respondentsof this study were 290 indonesianteenagers aged 18-20 year-old who are active on social media. Result of this study indicatesthat neuroticism, self control, and emotional loneliness have significant effect on compulsiveinternet use. This study also indicates that further study is needed to determine other variableseffect such as health and psychosocial well being on compulsive internet use on teenagers.